Exploring Sodium Gluconate as a Highly Effective Organocatalyst for Dihydropyrano[2,3-c]Pyrazole Derivatives Synthesis - A. U. Khandebharad (Novel Aspects on Chemistry and Biochemistry Vol. 5, 2023)
This study aimed to investigate the potential of sodium gluconate, a versatile biomolecule, as an efficient and recyclable organocatalyst for synthesizing dihydropyrano[2,3-c]pyrazole derivatives. This eco-friendly protocol utilized a combination of aryl aldehyde, malononitrile, ethyl acetoacetate, and hydrazine hydrate in water. The use of sodium gluconate offered several advantages, including non-toxicity, easy separation, reusability, broad substrate scope, simple work-up, and high product yield, thereby highlighting its greener attributes.